Rippled blue phosphorene with tunable energy band structures and negative Poisson’s ratio - Rong Li; Hang Xiao; Yan Chen (AIP Advances, 2023)
Recent successes in the discovery of novel two-dimensional (2-D) phosphorene allotropes have motivated more in-depth investigations into tuning their properties through precise geometric control. This is also driven by the fact that these materials, particularly blue phosphorene, are highly prone to wrinkling. In this work, we systematically study the mechanical and electronic behaviors of a series of rippled blue phosphorene PN (N = 8, 18, 32, 50, 72, 98) using density functional theory combined with molecular dynamic simulations. A novel approach to tailor the electronic energy band structure of blue phosphorene is proposed by wrinkle engineering, transforming the native indirect bandgap into a direct bandgap, and enabling bandgap tuning by modifying the undulation magnitude ratio. Furthermore, the mechanical behaviors of rippled blue phosphorene differ significantly along the 4-8-4 and 4-4-4 directions. Notably, negative Poisson’s ratio is observed under tension along the 4-4-4 direction. This work demonstrates new techniques for geometrically regulating blue phosphorene and potentially other 2-D materials. The findings also yield valuable insights for the design of novel 2-D auxetic semiconductors with tunable electronic properties.